Interest in linkage to PrEP among people who inject drugs accessing syringe services; Miami, Florida - Jo, Young (PLoS One, 2020)
BACKGROUND: People who inject drugs (PWID) are at an increased risk for HIV infection due to injection and sexual risk behaviors. This study aims to examine PrEP knowledge, awareness, and willingness to be linked to PrEP services at a syringe services program (SSP), and examine the relationship between substance use and interest in PrEP linkage. METHODS: Data were collected using a cross-sectional survey of IDEA SSP clients in Miami, FL (N = 157). Based on reported substance injected, participants were classified into opioid-only injection or polysubstance injection. Socio-demographics and HIV risk were examined using Pearson’s Chi-Squared analysis. Bivariate and multivariable logistic regression models were used to test for significant correlates of interest in PrEP linkage. RESULTS: Only 28.3% of PWID surveyed had previously heard of PrEP. However, 57.2% were interested in receiving more information about PrEP. In the adjusted model, people with opioid-only use were significantly less likely to report interest in being linked to PrEP. CONCLUSION: Knowledge, awareness, and interest in being linked to PrEP were low among PWID surveyed. No participants of the study were successfully linked to PrEP services through direct referrals. Further research is needed to examine low threshold service delivery of PrEP to PWID at SSPs.